Antibacterial efficacy of berry juices against Bacillus cereus relative to their phytochemical composition and antioxidant properties - Kamil Królak; Sylwia Ścieszka; Edyta Kordialik-Bogacka; Joanna Oracz; Maciej Ditrych; Tomasz Szczygieł; Katarzyna Dybka-Stępień; Anna Otlewska; Dorota Żyżelewicz (Scientific Reports, 2024)
Abstract Ensuring the safety and stability of minimally processed foods using natural preservatives is of great scientific and commercial interest in modern biotechnology. Berry juice supplementation is increasingly recognized within this field. This study investigated the effectiveness of juices from four berry species Aronia melanocarpa, Ribes nigrum, Vaccinium macrocarpon, and Sambucus nigra, against the food pathogen Bacillus cereus. Overall, the antibacterial potency of juice supplements (up to 10% v/v in tryptic soy broth) followed the order of chokeberry > blackcurrant > cranberry > elderberry, with the latter showing no inhibitory effects. Notably, chokeberry and elderberry juices presented lower acidity and significantly greater phenolic contents (p < 0.05) than blackcurrant and cranberry juices did, suggesting that B. cereus susceptibility is not strictly dependent upon low extracellular pH or elevated anthocyanin levels. Instead, it is inferred to correlate with pro-oxidative effects induced directly at the intracellular level. Accordingly, this paper discusses the antioxidative, acidic, and lipophilic attributes of juices and their constituent fractions, including anthocyanins, to elucidate their biopreservative potential. The results of this study increase our understanding of the antibacterial susceptibility of B. cereus.